Development of an improved approach to transcatheter heart valve heart valve replacement in younger patients - Weich, Hellmuth Stephan von Heyderhoff (Stellenbosch : Stellenbosch University, 2024)
Thesis (PhD)--Stellenbosch University, 2024.